Analysis of factors influencing residents' waste sorting behavior: A case study of Shanghai - Govindan, Kannan; Zhuang, Yue; Chen, Gang (Journal of cleaner production, 2022)
Waste sorting is essential to alleviate the current municipal waste dilemma, and some countries have implemented waste management policies to encourage residents separating food waste at the source. In order to improve residents' participation rate in waste sorting, it's necessary to study the influencing factors of residents' waste sorting behavior. Therefore, this study built an extended theoretical research model based on the theory of planned behavior (TPB). A survey of 324 valid questionnaire responses in Shanghai was conducted to analyze the factors influencing residents' waste sorting behavior by using structural equation modelling. This research found that attitude, subjective norms, and perceived behavioral control were positively and significantly related to residents' waste sorting intention and proved sorting behavior is influenced by sorting intention. Meanwhile, the results suggested these three newly added factors (infrastructure, economic incentive, and assistance & supervision) have a positive moderating effect on the relationship between intention and behavior. This research advanced the understanding of residents' waste sorting behavior and improved TPB by adding three factors. Moreover, our study concluded important experience from a relatively successful case city of Shanghai, which provided valuable implications for promoting residents of other municipalities to participate in waste sorting.